1971
DOI: 10.1073/pnas.68.7.1516
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxanthine-Guanine Phosphoribosyltransferase Deficiency: Chemical Agents Selective for Mutant or Normal Cultured Fibroblasts in Mixed and Heterozygote Cultures

Abstract: Cultured fibroblasts established from skin biopsies from patients with the Lesch-Nyhan syndrome are deficient in hypoxanthine-guanine phosphoribosyl-transferase (EC 2.4.2.8) activity. This deficiency makes possible the use of chemicals that select either for or against deficient variants in cultured fibroblasts. Two-way selection has been achieved by the use of 6-thioguanine, which selects for the deficient mutant, and azaserine, which selects to some extent for the normal allele in mixed cultures, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

1972
1972
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…Metabolic cooperation was initially demonstrated by Subak-Sharpe et al, 28,29 who showed that hypoxanthine could only be incorporated in hypoxanthine/guanine phosphoribosyl transferase-deficient (HGPRT − ) cells when cocultured with HGPRT-positive cells, a process later shown to be mediated by gap junctional communication. Later, Fujimoto et al 30 demonstrated that HGPRT − cells became sensitive to the purine analogue 6-thioguanine in cocultures with HGPRT + cells. The same effect was observed with 8-azaguanine and adenine analogs with HGPRT − and adenine phosphoribosyl transferase-deficient (APRT − ) cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic cooperation was initially demonstrated by Subak-Sharpe et al, 28,29 who showed that hypoxanthine could only be incorporated in hypoxanthine/guanine phosphoribosyl transferase-deficient (HGPRT − ) cells when cocultured with HGPRT-positive cells, a process later shown to be mediated by gap junctional communication. Later, Fujimoto et al 30 demonstrated that HGPRT − cells became sensitive to the purine analogue 6-thioguanine in cocultures with HGPRT + cells. The same effect was observed with 8-azaguanine and adenine analogs with HGPRT − and adenine phosphoribosyl transferase-deficient (APRT − ) cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These HGPT-cells, normally resistant to 6-TG, became sensitive to 6-TG when cocultured with HGPT+ fibroblasts. They suggested that metabolic coupling resulted in the transfer of toxic metabolites to the HGPT-cells, a process they termed "the kiss of death" (27). Electron microscopy and microinjection experiments have shown that intercellular gap junctions are present in cells demonstrating metabolic coupling (28,29 Previous studies have found no injury to normal cells surrounding tumors treated with GCV after HSV-tk gene transfer (31).…”
Section: Methodsmentioning
confidence: 99%
“…The concept of metabolic coupling was proposed in 1969 (26) to describe intercellular transfer of molecules that alter the metabolism of recipient cells. Fujimoto et al (27) used 6-thioguanine (6-TG) to select fibroblasts lacking hypoxanthine/guanine phosphoribosyltransferase (HGPT). These HGPT-cells, normally resistant to 6-TG, became sensitive to 6-TG when cocultured with HGPT+ fibroblasts.…”
Section: Methodsmentioning
confidence: 99%
“…(Loewenstein & Kanno, 1964). The reports of Fujimoto et al (1971) and Corsaro and Migeon (1977) provide ample evidence that the communication which exists between coupled cells in monolayer culture is sufficiently extensive to allow transfer of 6-thioguanine sensitivity or oubain resistance.…”
mentioning
confidence: 99%
“…In some cases where the interaction is between drug-sensitive and -resistant subpopulations, the mechanism underlying this phenomenon is clear, as in the cases of transfer of thioguanine sensitivity by cell-to-cell transfer of thioguanine nucleotides (Fujimoto et al, 1971) or of ouabain resistance by transfer of cytoplasmic Na+ and K+ (Corsaro & Migeon, 1977). In other cases the mechanism of interaction remains obsure or poorly defined (Miller et al, 1981;Tofilon et al, 1984Tofilon et al, , 1987.…”
mentioning
confidence: 99%